Australian freshwater sponges with a new species of Pectispongilla (Porifera: Demospongiae: Spongillida) - Manconi, R.; Cubeddu, T.; Pronzato, R. (Zootaxa, 2016)
This paper focus on the biodiversity assessment of Australian inland water. Checklists of Australian Spongillida are also provided with biogeographic notes together with the geographic range of all species of freshwater sponges in Australia. New discoveries on freshwater sponges are reported from ephemeral freshwater habitats in Kakadu National Park (Australia Northern Territory). Morphological analyses show that the sponges belong to Radiospongilla and Pectispongilla in the family Spongillidae. Radiospongilla cfr. philippinensis shows a single layer of radial gemmuloscleres and the absence of tangential gemmuloscleres in the gemmular theca. Pectispongilla gagudjuensis n. sp. diverges from the diagnostic traits of the four species currently assigned to the genus i.e. skeletal megascleres are dominant acanthostrongyles and less frequent acanthoxeas shorter than in the other species, microscleres are absent, and gemmules are larger than in the other species of the genus.